Lendo fábulas e ampliando a competência leitora: uma proposta para a educação de jovens e adultos - Souza, Andréa Garcia de (2020)
Concerning to the teaching of the Youth and Adult Education (EJA) students, it is possible to observe the difficulty they present in reading efficiently and autonomously. Based on this fact, the objective of this work is to contribute to the development of reading competence of 2nd Cycle of Youth and Adult Education students of a school in the municipality of Bayeux-PB, suported by Solé reading strategies applied to the fable gender, having reading skills Indicated by the Common National Curriculum Base for the Early Years of Elementary School. A research aimed at the student group involved, addressing a thematic reading, is justified by the learning gaps that manifest in relation to the advanced skills of this practice, a finding of public historical exclusion of this audience and recognition of reading proficiency is an important instrument of social participation. The theoretical foundation of this study was carried out in Koch and Elias (2017) and Bonifácio (2015) to address reading conceptions, in Solé (1998) to support the teaching of reading strategies, in Yunes (1995) to relate citizenship and reading, in Cabral (1986) to name some reading skills, in Kleiman (2005) for literacy treatment, in Freire (1987, 1989), Gadotti and Romão (2011) to reflect on the subject-student of EJA and the teacher formation , in Bakhtin (1997), Marcuschi (2008), Portella (1983), Silva (2010) and Bagno (2006) to discuss discursive and fable genre. Regarding the fabulists, it was decided to work with Esopo (1997), La Fontaine (2011), Lobato (2019) and Millôr Fernandes (1999). This research is interventionist in nature, with a qualitative approach, characterized as action research. In the beginning, it was made a Diagnostic Activity to verify the level of the students´s reading skills and, from the information gathered, it was made a Pedagogical Intervention that took place through Reading Workshops. After the workshops, another diagnostic activity was done for comparison with the initial diagnostic one. The result of this comparison was positive in relation to the intended research objective of the two diagnosed activities mentioned in the corpus.